Read to tiger - Fore, S. J.; Alley, R. W. (Robert W.) (New York : Viking, 2010)
A little boy who wants to read his book keeps being distracted by a tiger who is busy chomping on gum, growling, and practicing karate kicks.
Keywords: Books and reading -- Fiction; Tiger -- Fiction